Riding with the Revolution : The American Left in the Mexican Revolution, 1900-1925 - Botz, Dan La (Historical Materialism Book Series, 2024)
Riding with the Revolution tells the story of Americans who from 1900 to 1925 became involved with the Mexican Revolution. John Reed actually saddled up and rode with Pancho Villa. Later, American war resisters crossed the Rio Grande into Mexico